Increased Participation in Weekend Physical Activity Reduces Postprandial Lipemia in Postmenopausal Women - Miyashita, M.; Takahashi, M.; Burns, S. (International Journal of Sports Medicine, 2014)
This study examined the acute effect of increased participation in weekend physical activity on postprandial lipemia in postmenopausal women. Ten postmenopausal women, aged 63±4 years (mean±SD), completed 2 trials in a random order: 1) control trial and 2) active trial. In the control trial, participants maintained their usual weekend lifestyle. In the active trial, participants increased their weekend activities above their usual lifestyle levels, freely deciding the duration and intensity of their chosen activities. On Monday of each trial, participants rested and consumed a standardised breakfast and lunch. Capillary blood samples were collected in the fasted state (0 h) and at 2, 4 and 6 h after eating. In the active trial, participants increased their moderate to vigorous weekend physical activity by 16 min (mean±SD: 12.3±6.7 min vs. 27.9±11.9 min, P=0.009). Area under the capillary triacylglycerol concentration vs. time curve was 13% lower in the active trial than control trial (8.8±3.8 vs. 10.1±3.9 mmol/L∙6 h, P=0.024). These findings demonstrate that small increases in moderate to vigorous physical activity under a real-life setting lowers postprandial lipemia in postmenopausal women.
Keywords: physical activity; postprandial triacylglycerol; real-life setting; postmenopausal women